Na,K-ATPase Isozymes in Colorectal Cancer and Liver Metastases - Baker Bechmann, Marc; Rotoli, Deborah; Morales, Manuel; Maeso, María del Carmen; García, María del Pino; Ávila, Julio; Mobasheri, Ali; Martín-Vasallo, Pablo (Frontiers in Physiology, 2016)
The goal of this study was to define Na,K-ATPase α and β subunit isoform expression and isozyme composition in colorectal cancer cells and liver metastases. The α1, α3 and β1 isoforms were the most highly expressed in tumor cells and metastases; in the plasma membrane of non-neoplastic cells and mainly in a cytoplasmic location in tumor cells. α1β1 and α3β1 isozymes found in tumor and metastatic cells exhibit the highest and lowest Na+ affinity respectively and the highest K+ affinity. Mesenchymal cell isozymes possess an intermediate Na+ affinity and a low K+ affinity. In cancer, these ions are likely to favor optimal conditions for the function of nuclear enzymes involved in mitosis, especially a high intra-nuclear K+ concentration. A major and striking finding of this study was that in liver, metastasized CRC cells express the α3β1 isozyme. Thus, the α3β1 isozyme could potentially serve as a novel exploratory biomarker of CRC metastatic cells in liver.